Pengaruh Pijat Bayi terhadap Peningkatan Berat Badan Bayi Usia 3-6 Bulan di Wilayah Kecamatan Kedawung Kabupaten Sragen Jawa Tengah Tahun 2022: Influence of Infant Massage on The Growth (Weight) of Infants Aged 3-6 Months in The Region of kedawung District, Sragen Regency, Central Java, in 2022 - Putri Darwati; Ninik Christiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2022)
The percentage of low birth weight babies (LBW) in Central Java in 2020 was 10.45 percent, while for the Sragen district itself in 2020 it was 9.2 percent. increased when compared to the percentage in 2019. Effortscan be made to optimize the baby's weight in addition to the nutrition providedby the mother and one way is the need for stimulation or commonly known as baby massage. Based on a preliminary study conducted in the Kedawung District, Sragen Regency, Central Java, there were several babies who experienced weight loss. To determine the effect of baby massage on the growth (weight) of infants aged 3-6 months in Sragen Regency, Central Java in 2022. This study aims to determine the effect of baby massage on the growth (weight) of infants aged 3-6 months in Sragen Regency, Central Javain 2022.The research method used for this proposal is a quasi-quantitative experiment (quasi-experimental) with a non-equivalent control groupdesign.This experiment was carried out on infants aged 3-6 months in the Kedawungsub- district, Sragen district, Central Java. The sample was divided into two groups, namely the intervention group 20 and the control group 20. From the results of research, demographic data of respondents, the average body weight of respondents before and after massage, namely before massage in the intervention group was 6.882 g and experiencedweight gain after massage with an average of 7.378 g, while in the control group the average weight before massage was was 6.602 g and after a massage experienced an average weight gain of 6.914 g. The results of the paired-t testobtained p value = 0.000, statistically p value = 0.000 < or 0.05 then Ho is rejected and Ha is accepted. It can be concluded that there is an effect of baby massage on increasing infant weight in the ah district of Kedawung district, Seragen district. ABSTRAKPersentase bayi berat lahir rendah (BBLR) di Jawa Tengah pada tahun 2020 sebesar 10,45 persen, sedangkan untuk Kabupaten Sragen sendiri pada tahun 2020 sebesar 9,2 persen. meningkat bila dibandingkan dengan persentase tahun 2019. Upaya yang dapat dilakukan dalammengoptimalkan berat badan pada bayi di samping nutrisi yang diberikan oleh ibu, ada cara lain yaitu adanya rangsangan stimulus pada bayi yang biasa dikenal dengan pijat bayi. Berdasarkan studi pendahuluan yang dilakukan di wilayah Kecamatan Kedawung Kabupaten Sragen Jawa Tengah terdapat beberapa bayi yang mengalami penurunan berat badan pada 1 bulan pertama kelahirannya dengan berbagai faktor penyebab.Untuk mengatasi hal tersubut diperlukan adanya rangsangan pijat bayi untuk bayi dalam meningkatkan berat badannya. Untuk mengetahui pengaruh pijat bayi terhadap peingkatan berat badan bayi usia 3-6 bulan di wilayah Kabupaten Sragen Jawa Tengah tahun 2022.Metode penelitian yang digunakan adalah quasi eksperimen kuantitatif (eksperimen semu) dengan rancangan non equivalen kontrol group. Eksperimen ini dilakukan pada bayi usia 3-6 bulan yang berada di wilayah kecamatan kedawung kabupaten sragen jawa tengah. Sampel dibagi menjadi dua kelompok yaitu kelompok intervensi 20 dan kelompok kontrol 20. Dari hasil penelitian data demografi responden didapat rata-rata beratbadan responden sebelum dan sesudah dipijat yaitu sebelum dipijat pada kelompok intervensi adalah 6.882 gr dan mengalami kenaikan berat badan setelah dipijat dengan rata-rata 7.378 gr sedangkan pada kelompok kontrol rata-rata berat badan sebelum dipijat adalah 6.602 gr dan setelah dipijat mengalami kenaikan berat badan rata-rata 6.914 gr. Hasil uji paired-t test diperoleh nilai p=0,000, secara statistik nilai p=0,000 < atau 0,05 maka Ho ditolak dan Ha diterima. Dapat disimpulkan ada pengaruh pijat bayi terhadap peningkatan berat badan bayi di wilayahah kecamatan kedawung kabupaten Sragen.